ANALISIS SASTRA ANAK DALAM CERKAK MAJALAH PANJEBAR SEMANGAT EDISI (1 – 53) TAHUN 2016 SERTA RELEVANSINYA SEBAGAI MATERI PEMBELAJARAN APRESIASI SASTRA SISWA SMK (SEBUAH PENDEKATAN SOSIOLOGI SASTRA) - Agnesia Levirosa Putri; Budi Waluyo; Rahmat Rahmat (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2018)
This research aimed to (1) describe and explain the intrinsic elements contained in the cerkak - cerkak of the Panjebar Semangat magazine on the Edition (1 - 53) in 2016; (2) describe the social condition of the society contained in the cerkak-cerkak of the Panjebar Semangat magazine on the Edition (1 - 53) in 2016; (3) Describe and explain the relevance of the cerkak-cerkak of the Panjebar Semangat magazine on the Edition (1 - 53) in 2016. This was a qualitative research with descriptive qualitative method. The sources of the data in this study were documents and informants. The validity of the data was triangulation theory and the source. The sampling technique used in this research was purposive sampling technique. Technique of collecting data used reading and interviewing techniques. There were 4 Data analysis techniques used in this research, those were domain analysis, taxonomy, component, theme and cultural. Based on the results of the research and discussion written on chapter IV about cerkak analysis, social condition of the society, and the relevance as learning material of literature appreciation subject on high school student, it was concluded that the analysis of 6 cerkak containing child literature element was suitable to read for student.